Rebuilding Micro-Enterprises Identity through Sharing Economy: Empirical Evidence from the Perspective of Innovation Diffusion and Perceived Social Value - Ngian, Ek Tee; Ling, Pick-Soon (International Review of Management and Marketing, 2025)
This study empirically validated the proposed research framework to predict micro-enterprises intention to rebuild their identity by embracing the sharing economy platform. Micro-enterprises have been affected by Covid-19 and thus, it necessitates strategies to rebuild identity and regain market competitiveness. However, evidence of micro-enterprises effectively leveraging the sharing economy remains under-researched. To address this gap, the proposed framework draws upon the Innovation Diffusion Theory (IDT) and investigates five key innovation attributes: relative advantage, compatibility, complexity, observability, and trialability towards the perceived social value (PSV) and behavioural intention (BI) to rebuild identity through the sharing economy. By analysing 171 valid responses from the micro-enterprises in Malaysia, the result of the partial least squares-structural equation modelling revealed that out of the five innovation attributes, only observability and trialability have a positively significant effect on the PSV, while the BI to rebuild identity through sharing economy is positively significant affected by PSV. Additionally, the finding also showed that PSV significantly mediated the influence of observability toward BI to rebuild identity. The study contributes theoretically by filling the research gaps in the existing knowledge and offering practical implications for policymakers and micro-enterprises to devise strategies and policies in adopting digital innovations to rebuild their identity in post-pandemic.